SHARPENINGS OF JENSEN’S INEQUALITY AND APPLICATIONS - Dragomir, S. S.; Arslanagić, Š. Z.; Milošević, D. M. (Matematichki Bilten, 1996)
Some new refinements of the well known Jansen’s inequality and certain natural applications are given.